H2S Donor and Bone Metabolism - Yanming Hao; Hongzhen Wang; Lingna Fang; Jinsong Bian; Yan Gao; Chong Li (Frontiers Media S.A., 2021)
Hydrogen sulfide (H2S) has been recognized as the third gasotransmitter, following nitric oxide and carbon monoxide, and it exerts important biological effects in the body. Growing evidence has shown that H2S is involved in many physiological processes in the body. In recent years, much research has been carried out on the role of H2S in bone metabolism. Bone metabolic diseases have been linked to abnormal endogenous H2S functions and metabolism. It has been found that H2S plays an important role in the regulation of bone diseases such as osteoporosis and osteoarthritis. Regulation of H2S on bone metabolism has many interacting signaling pathways at the molecular level, which play an important role in bone formation and absorption. H2S releasing agents (donors) have achieved significant effects in the treatment of metabolic bone diseases such as osteoporosis and osteoarthritis. In addition, H2S donors and related drugs have been widely used as research tools in basic biomedical research and may be explored as potential therapeutic agents in the future. Donors are used to study the mechanism and function of H2S as they release H2S through different mechanisms. Although H2S releasers have biological activity, their function can be inconsistent. Additionally, donors have different H2S release capabilities, which could lead to different effects. Side effects may form with the formation of H2S; however, it is unclear whether these side effects affect the biological effects of H2S. Therefore, it is necessary to study H2S donors in detail. In this review, we summarize the current information about H2S donors related to bone metabolism diseases and discuss some mechanisms and biological applications.